The effect of various media on growth of ebony (Diospyros celebica Bakh) seedlings through seeds multiplication - NURUL SUMIASRI; NINIK SETYOWATI (Biodiversitas Journal of Biological Diversity, 2006)
Study of the effects of various media on growth of ebony (Diospyros celebica Bakh) seedlings through seeds multiplication was carried out. The experiment used various media i.e. sands, soil (latosol), compost and EM Bokashi. The study was arranged by Factorial Randomized Block Design with 4 replications, growth parameters were observed i.e. growth percentage, plant height, total leaves, total roots and rootslength. The results showed that the best medium of all parameter observed was EM Bokashi and the low results showed by latosol soil medium. Statistically all of parameter observed showed significant level at 5% Duncansâ€™ tested to various media. The best media at the study was EM Bokashi, and could be recommended for media of ebony seed multiplication especially.Â© 2006 Jurusan Biologi FMIPA UNS SurakartaKey words: effect, media, growth, seedling, ebony multiplication.